An Indirect Comparison Between Nivolumab + Ipilimumab + Two Cycles of Chemotherapy vs. Pembrolizumab + Chemotherapy as First-Line Treatment for Metastatic Non-Small Cell Lung Cancer - Jiang, Panpan; Mao, Ziyang; Wang, Qinyang; Jia, Xiaohui; Geng, Luying; Xu, Hong; Jiang, Lili; Yang, Chengcheng; Jiao, Min; Guo, Hui (Frontiers in Oncology, 2021)
Background: Nivolumab + ipilimumab + two cycles chemotherapy (N-I + chemo, intensive immunotherapy but chemo-light) and Pembrolizumab + chemotherapy (Pem + chemo) were both recommended as first-line treatment for metastatic non-small cell lung carcinoma (NSCLC) patients. We conducted this indirect comparison to compare the efficacy of and safety between these two treatments for providing reference for decision making. Methods: Relevant databases were searched for eligible trials. A well-accepted adjusted indirect treatment comparison (ITC) approach was selected to pooled efficacy results and safety outcomes. Subgroup analyses were stratified according to PD-L1 expression and clinical characteristics. Results: 4 eligible randomized trials (CheckMate9LA, KEYNOTE-021G, KEYNOTE 189, KEYNOTE 047) involving 2017 patients were available to analyze. The ITC results suggested that N-I + chemo is comparable to Pem + chemo in OS (HR 1.03, 95% CI 0.82-1.30 ) and ORR (RR 0.81, 95% CI 0.63-1.03), but tended to yield inferior PFS (HR 1.28, 95% CI 1.04-1.59) than did Pem + chemo. As for safety profiles, N-I + chemo showed no significant difference relative to Pem + chemo in any grade adverse events: RR 1.03, 95% CI 0.98-1.09), but demonstrated reduced toxicity in chemo-related adverse events, such as anemia (RR 0.63, 95% CI 0.49-0.81), neutropenia (RR0.51, 95% CI 0.33-0.79), thrombocytopenia (RR 0.38, 95% CI 0.21-0.69). Conclusions: N-I + chemo is a promising treatment option for providing comparable OS relate to Pem + chemo. However, for never smoker female patients, Pem + chemo is preferable to choose for demonstrating favourable OS benefit than N-I + chemo.